Effect of Ergonomic Exercise on Blood Glucose Levels and Anxiety in Type 2 Diabetes Mellitus Patients. - Muhaimin, Ahmad; Rohman, Handono Fathur; Fauzi, Ahmad Kholid (Adult Health Nursing Journal, 2024)
Introduction: The majority of DM patients have less knowledge about DM disease, including how to control blood sugar levels and lack of awareness of healthy living behavior, which is one of the causes of complications of DM disease, namely how to control blood glucose levels to avoid complications and this makes The patient becomes anxious about these complications.  Objectives: To determine the effect of ergonomic exercise on blood glucose levels and anxiety of clients with type 2 diabetes mellitus at the Jatibanteng Health Center Situbondo. Methods: This research method uses a quasi-experimental design. The population in this study were 150 diabetes mellitus patients at the Jatibanteng Situbondo Health Center. Samples were taken using purposive sampling technique as many as 109 respondents. Data were collected with the HARS scale questionnaire instrument for anxiety and GDA examination for the patient's blood sugar levels and tested by paired t test. Results: The results showed that there was a decrease in the average score in the experimental group by 19,783 greater than the control group = 6,633 so this indicated that ergonomic strings were more effective in reducing anxiety in people with diabetes mellitus. Based on the results of the Kolmogorov Smirnov normality test, it showed a value of ρ > α = 0.05 so that the data was normally distributed and the test used was the paired t test as a parametric test. The results of the paired t test showed a significant value for both groups ρ = 0.000 < α = 0.05 so that H0 was rejected and H1 was accepted, meaning that there is an effect of ergonomic gymnastics on the anxiety of diabetes mellitus patients at the Jatibanteng Health Center Situbondo. Conclusions: Ergonomic gymnastics can be used as an alternative to providing physical exercise for people with diabetes mellitus.